Enantioselective CuH-Catalyzed Hydroallylation of Vinylarenes - Wang, Yi-Ming (J Am Chem Soc, 2016)
[Image: see text] The enantioselective, intermolecular hydroallylation of vinylarenes employing allylic phosphate electrophiles has been achieved through a copper hydride catalyzed process. The protocol described herein can be applied to a diverse set of vinylarene substrates and allows for the installation of the parent allyl group as well as a range of 2-substituted allylic fragments.